Evaluation of Working Postures at a Garden Maintenance Service to Reduce Musculoskeletal Disorder Risk (A Case Study of PT. Dewijaya Agrigemilang Jakarta) - Adisty Savitri; Guntarti Tatik Mulyati; Ibnu Wahid Fakhrudin Aziz (APTA and DTIP FTP UGM, 2017)
This research is carried out in order to evaluate the working postures of seven workers withdifferent job categories at a garden maintenance service. These seven categories of works aredivided into 23 work elements. The aim of this research is to investigate the presence of work-related pain symptoms, find all risk related to poor working postures, and finally propose sets ofrecommendations for improvement of working methods. Nordic Body Map questionnaire is usedin the study to detect the occurrences of workrelated pain. Meanwhile, risk level assessment forworking postures was carried out by means of Rapid Entire Body Assessment (REBA) method.All the two applied on seven job categories of workers.The results showed that all workers observed experienced with pain symptoms both after and before carry out the work. According to REBA analysis, there are 82.6% medium level risk working elements, 10.9% high level risk, 4.3% very high level risk, and 2.2% low level risk. Recommendation for improvement of working posture was given for work element, namely fertilizer sowing(very high level risk), hedge trimming (high level risk), and pesticide spraying (high level risk).Implementation of these proposed improvements result on diminishing the frequency of occurrence and the level of risk on physical pain.